2020
DOI: 10.1002/jpen.1960
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Metabolic Improvement After Roux‐en‐Y Gastric Bypass May Include a Compensatory Mechanism That Balances Fatty Acid β and ω Oxidation

Abstract: Background: More than half of patients who undergo Roux-en-Y gastric bypass (RYGB) can experience type 2 diabetes (T2D) remission, but the systemic and gastrointestinal (GI) metabolic mechanisms of this improvement are still elusive. Methods: Paired samples collected before and 3 months after RYGB from 28 women with obesity and T2D were analyzed by metabolomics with gas chromatography coupled to mass spectrometry. Samples include plasma (n = 56) and biopsies of gastric pouch (n = 18), gastric remnant (n = 10),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Numerous studies demonstrated that circulating levels of valine [ 17 34 ], isoleucine [ 17 24 , 26 , 27 , 29 36 ], leucine [ 17 24 , 26 , 27 , 29 33 , 35 37 ], phenylalanine [ 17 , 18 , 20 , 21 , 23 , 24 , 26 29 , 37 ], tyrosine [ 17 21 , 23 , 24 , 27 , 29 , 30 , 37 ], tryptophan [ 17 , 21 , 24 , 29 , 37 , 38 ], alanine [ 17 21 , 23 , 28 , 30 , 33 , 39 ], proline [ 17 19 , 21 , 28 , 39 ], methionine [ 18 , 23 , 30 ], aspartate [ 21 ], threonine [ 19 , 21 , 32 ], lysine [ 19 ] and ornithine [ 18 , 21 , 24 , 30 , 40 ] decrease after bariatric surgery. Contrarily, circulating levels of glycine [ 18 22 , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies demonstrated that circulating levels of valine [ 17 34 ], isoleucine [ 17 24 , 26 , 27 , 29 36 ], leucine [ 17 24 , 26 , 27 , 29 33 , 35 37 ], phenylalanine [ 17 , 18 , 20 , 21 , 23 , 24 , 26 29 , 37 ], tyrosine [ 17 21 , 23 , 24 , 27 , 29 , 30 , 37 ], tryptophan [ 17 , 21 , 24 , 29 , 37 , 38 ], alanine [ 17 21 , 23 , 28 , 30 , 33 , 39 ], proline [ 17 19 , 21 , 28 , 39 ], methionine [ 18 , 23 , 30 ], aspartate [ 21 ], threonine [ 19 , 21 , 32 ], lysine [ 19 ] and ornithine [ 18 , 21 , 24 , 30 , 40 ] decrease after bariatric surgery. Contrarily, circulating levels of glycine [ 18 22 , …”
Section: Resultsmentioning
confidence: 99%
“…Likewise, an increase in ketone bodies (3-hydroxybutyrate and acetoacetate) levels was also identified after bariatric surgery [ 19 , 27 , 37 , 38 , 43 , 51 ]. Although, carboxylic acids and ketone bodies levels were only observed or were more pronounced in short-term period after surgery [ 22 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations